Development and first evaluations of a novel preventive knee brace for alpine skiracing - Spitzenpfeil, P.; Olvermann, M.; Senner, V.; Nusser, M.; Diez, L.; Junior, V.; Huber, A.; Waibel, K.; Moritz, E. F.; Stehling, G.; Semsch, H.; Brucker, P. U. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Although knee injuries are the major injury type in alpine skiing (Flørenes 2012) up to now, contrary to head and spine, there are no preventive accessories like helmet and back protector. In a 2-years process our group developed a new knee brace in combination with special underwear for preventive use. The first braces have already been delivered to world cup athletes and in this paper the development process and first evaluation results are documented.